Probing protein-protein interactions with peptide libraries and arrays - Songyang, Zhou (Henry Stewart Talks, 2008)
Protein-protein interactions as key to understanding signaling pathways, Signaling through tyrosine phosphorylation, Using peptide libraries to study specificities of protein modules, Peptide library arrays (OPAL), OPAL strategies, examples and advantages
Archived at 2021/02/25